Interpretations of Reagan’s Legacy - Balogh, Máté Gergely (Hungarian Journal of English and American Studies, 2020)
Book review:Chidester, Jeffrey L., and Paul Kengor, eds. Reagan’s Legacy in a World Transformed. Cambridge, MA: Harvard UP, 2015. 294 pages. ISBN 978-0-674-42620-7. Hb. $45.